2014
DOI: 10.1016/j.immuni.2014.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Gene Atg16l1 Prevents Lethal T Cell Alloreactivity Mediated by Dendritic Cells

Abstract: SUMMARY Atg16L1 mediates the cellular degradative process of autophagy and is considered a critical regulator of inflammation based on its genetic association with inflammatory bowel disease. Here we find that Atg16L1 deficiency leads to an exacerbated graft-versus-host disease (GVHD) in a mouse model of allogeneic hematopoietic stem cell transplantation (allo-HSCT). Atg16L1-deficient allo-HSCT recipients with GVHD displayed increased T cell proliferation due to increased dendritic cell (DC) numbers and co-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 52 publications
(66 reference statements)
2
81
0
Order By: Relevance
“…Compared with the UGI tract, the colon hosts most anaerobic microorganisms at very high density (10 2 -10 3 versus 10 11 -10 12 bacteria/gram luminal contents) [29,30]. The role of microbiome in GI GVHD has been shown in several animal studies [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the UGI tract, the colon hosts most anaerobic microorganisms at very high density (10 2 -10 3 versus 10 11 -10 12 bacteria/gram luminal contents) [29,30]. The role of microbiome in GI GVHD has been shown in several animal studies [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…50 In a mouse model of graft versus host disease, deletion of Atg16l1 resulted in global dendritic cell activation, leading to increased T cell stimulation. 51 On the other hand, dendritic cells lacking Atg5 were unable to induce the differentiation of cytokine-producing CD4 + T cells during T. gondii infection. 52 Furthermore, dendritic cells from CD patients carrying risk variants in NOD2 and ATG16L1 showed defects in autophagy induction and MHC-II antigen presentation.…”
Section: Cell Type-specific Roles Of Autophagymentioning
confidence: 99%
“…Autophagy plays an important role in several T cell-specific functions, including development, polarization, and memory. 51, 54-58 …”
Section: Cell Type-specific Roles Of Autophagymentioning
confidence: 99%
“…Intracellular antigen presentation via MHC class I molecules is also regulated by the autophagy machinery, because autophagy‐related proteins enhance MHC class I internalization for degradation and thereby diminish antigen display on the cell surface 268. Indeed, in vivo studies have primarily found enhanced CD8 + T cell responses in mice with defective autophagy in antigen‐presenting cells268, 269, 270 A potential mechanism leading to such increased CD8 + T cell expansions is that, in the absence of autophagy, more substrate becomes available for canonical MHC class I loading271 or by decreased endocytosis and degradation of cell surface MHC class I molecules 268. Thus, defective autophagy in skeletal muscle fibers could drive increased MHC class I expression and CD8 + T cell accumulation.…”
Section: Degenerative Pathomechanisms In Ibmmentioning
confidence: 99%